Counteracting the Social Media: The Role of Islamic Education Teachers' at SMAN 4 Tana Toraja - Salina Pasiangan; Hasbi Hasbi; Fauziah Zainuddin (International Journal of Asian Education, 2020)
This study aimed to analyze social media use in students and map Islamic education teachers' role in counteracting social media's negative impact on students at SMAN 4 Tana Toraja. This research uses a qualitative approach; The research subjects are the principal, Islamic Education teachers, students, and other teachers. The data collection technique involves observing, interviewing, documenting, and data analysis techniques with three stages: data reduction, data display, and data verification. The result findings on the research that social media use has their views, but most students use social media as a tool to get updated information, both related to education or outside education. Social media's impact also depends on the students; if the students use social media for good acts, it will positively impact, but it will impact negatively when the students use it in criminal activity. Islamic education teachers at SMA Negeri 4 Tana Toraja responsibility for providing understanding to the students about the impact of using social media. The responsibility of Islamic education teachers manifested in the character formation of students with noble character. Another finding is that the teachers must be able to divide their time to organize their roles properly. All forms of academic administration are expecting to immediately address so that the teacher's role problems can run optimally. the recommendation about the research is that students' use of social media must also go through the parent's and teachers' collaboration supervision empowerment